El antisemitismo en el refranero y en el léxico españoles (PHRASIS | Rivista di studi fraseologici e paremiologici, 2020)
The aim of this article is to study the figure of the Jew in the Spanish paremiology and lexicon, as well as the negative stereotypes that characterize it. The Spanish proverbs and lexicon abound in anti-Jewish terms, expressions and outbursts. A brief historical overview is given concerning Spanish Jews, and a corpus of sayings is analyzed, in order to testify how Christians saw the Jews, distinguishing various common places that underlie this cultureme, from the image of bad blood to all kinds of religious, economic and racist accusations, which have remained reflected in the vocabulary and in the paremiological heritage.
Keywords: Antisemitism, Judeophobia, anti- Zionism, racism, Spanish Collection of Proverbs